Mitigating urban heat island effects: a review of innovative pavement technologies and integrated solutions - Ismael, S. F.; Alias, A. H.; Haron, N. A.; Zaidan, B. B.; Abdulghani, Abdulrahman M. (Tech Science Press, 2024)
In this review paper, we present a thorough investigation into the role of pavement technologies in advancing urban sustainability. Our analysis traverses the historical evolution of these technologies, meticulously evaluating their socio-economic and environmental impacts, with a particular emphasis on their role in mitigating the urban heat island effect. The evaluation of pavement types and variables influencing pavement performance to be used in the multi-criteria decision-making (MCDM) framework to choose the optimal pavement application are at the heart of our research. Which serves to assess a spectrum of pavement options, revealing insights into the most effective and sustainable practices. By highlighting both the existing challenges and potential innovative solutions within the field, this paper aims to offer a directional compass for future urban planning and infrastructural advancements. This review not only synthesizes the current state of knowledge but also aims to chart a course for future exploration, emphasizing the critical need for innovative and environmentally sensitive pavement technologies in the creation of resilient and sustainable urban environments.